Effect of public health expenditure on health status in Ghana - Boachie, Micheal Kofi; Ramu, K. (International Journal of Health, 2016)
Health is an outcome indicator of economic growth and development of a country. Healthcare is a major factor for health status. In this regard, healthcare expenditure is a vital input for the health production function. In this context, this study examined the effect of public health expenditure on health status in Ghana. Annual time-series data on infant mortality rate, real per capita income, literacy levels and female labour force participation rate for the period 1990-2012 have been used. Infant mortality rate was used as the output variable. To test the relationship between input-output variables, Ordinary Least Squares and Newey-West regression techniques were used. The Â Â regression estimates suggest that real per capita income, public health expenditure, education and female presence in the labour market were negatively related to infant mortality rate. However, the elasticity coefficients of female participation in the labour market and real per capita income were statistically insignificant at 5% level. This study concludes that public health expenditure and literacy/education improve health status by reducing infant mortality. The favourable effect of education or literacy on health is greater than that of public health spending whereas the effect of real per capita come on health was found to be weak. The findings provide the impetus for government to raise literacy level and its health spending in the country to promote health.